Concentración mínima inhibitoria y concentración mínima bactericida In vitro del extracto etanólico de Piper acutifolium sobre Streptococcus pyogenes, ATCC 19615 - Neira Casana, Carlos Ivan (2018)
The aim of this research was to determine the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of the ethanolic extract of the leaves Piper acutifolium "matico" against Streptococcus pyogenes ATCC 19615. The minimum inhibitory concentration (MIC) it was evaluated by means of the macrodilution method in BHI medium (Brain Heart Infusion) and the bactericidal minin concentration (CMB) by agar dilution using the Mueller-Hinton agar surface technique. In the result obtained for CMI it was observed that as the concentration increases the degree of inhibition increases and for CMB the number of colonies decreases; this is due to the flavonoids present in the leaves of Piper acutifolium. The minimum inhibitory concentration (MIC) of the ethanolic extract of the leaves of Piper acutifolium on Streptococcus pyogenes ATCC 19615 in vitro was 0.66 mg / mL and the minimum bactericidal concentration (CMB) of the ethanolic extract of the leaves of Piper acutifolium on Streptococcus pyogenes, ATCC 19615 in vitro was 1 mg / mL